Decreased Westerly moisture transport leads to abrupt vegetation change in northern Central Asia during late MIS3: Evidence from Zeketai Loess, Ili Basin - Zhao, Shijin; Peterse, Francien; Chongyi, E; Lei, Yanyan; Huang, Miao; Yang, Huan; Xie, Shucheng (Elsevier BV, 2024)
Moisture transportation to (semi-)arid Central Asia is influenced by the interplay of multiple atmospheric circulation patterns. The mechanism underlying the hydroclimate evolution in CA has recently received increasing attention. In northeastern CA, most of the precipitation falls in summer, counter to other westerly-dominated regions of CA where precipitation maximizes in boreal winter. The marine isotope stage (MIS) 3 offers a unique opportunity to examine the mechanisms driving hydroclimate variations during warm periods of the ice age in the CA. However, due in part to reliable proxies for reconstruction, the hydroclimate and vegetation change during MIS3 in northeastern CA have not been well studied. Here, we use grain size and magnetic susceptibility data from the Zeketai loess profile to reconstruct historical shifts in precipitation patterns during MIS3 in the Ili Basin from arid Central Asia (ACA). Notably, abrupt changes around 35 ka are evident in the grain size and magnetic susceptibility records, reflecting a transition to reduced wind intensity and increased aridity. Subsequent analysis of plant leaf waxes (n-alkanes), hydrogen isotopic composition of n-alkanes (δDn-alkane), and stable carbon isotope ratios of total organic carbon (δ13Corg) within the loess profile indicates a concurrent shift towards more shrubs, aligning with reduced moisture availability. The δ13Corg record further elucidates that during MIS3, the Ili Basin predominantly harbored C3 vegetation. However, the alteration in δ13Corg and δDn-alkane to more positive values at approximately 35 ka substantiates the transition to more drought-resistant vegetation. Furthermore, we link the paleo-hydroclimate variations to the decrease in solar radiation and the strengthening of the Atlantic Meridional Overturning Circulation (AMOC) and Siberian High during late MIS3. This joint influence weakens the Westerly winds and subsequently diminishes the conveyance of moisture to CA.
Keywords: Hydroclimate; Ili loess; Marine isotope stage 3; Northern Central Asia; Stable carbon isotope; Westerlies; Taverne; Earth-Surface Processes; Ecology, Evolution, Behavior and Systematics; Oceanography; Palaeontology; SDG 14 - Life Below Water